2013
DOI: 10.3109/10641963.2013.780066
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren Reduces Morning Blood Pressure in Hypertensive Patients with Diabetic Nephropathy on Hemodialysis

Abstract: Our previous study indicated that the exchange from an angiotensin receptor blocker (ARB) to aliskiren reduced morning blood pressure and albuminuria in hypertensive patients with diabetic nephropathy. We extended the above study and assessed the effects of exchanging from an ARB to aliskiren on home blood pressure in hypertensive patients with diabetic nephropathy on chronic hemodialysis. The patients who were persistently hypertensive despite antihypertensive therapy, including ARB, were considered as candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In 2008, a new class of hypertension medications was approved for use in Canada, called direct renin inhibitors. Currently, aliskiren is the only medication within this class approved for use and appears to have weight neutral effects (0.0–1.0 kg 176 , 178 ).…”
Section: Antidepressantsmentioning
confidence: 99%
“…In 2008, a new class of hypertension medications was approved for use in Canada, called direct renin inhibitors. Currently, aliskiren is the only medication within this class approved for use and appears to have weight neutral effects (0.0–1.0 kg 176 , 178 ).…”
Section: Antidepressantsmentioning
confidence: 99%
“…Takenaka et al . reported that the alsikiren reduced morning blood pressure measured at home in HD patients with diabetic nephropathy [26]. These lines of evidence suggested that alsikiren has beneficial effects for blood pressure control in HD patients.…”
Section: Direct Renin Inhibitor In Hd Patinetsmentioning
confidence: 99%